2015
DOI: 10.1111/joop.12119
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of workplace coaching: A meta‐analysis of learning and performance outcomes from coaching

Abstract: This study presents a meta-analysis synthesizing the existing research on the effectiveness of workplace coaching. We exclusively explore workplace coaching provided by internal or external coaches and therefore exclude cases of manager-subordinate and peer coaching. We propose a framework of potential outcomes from coaching in organizations, which we examine meta-analytically (k = 17). Our analyses indicated that coaching had positive effects on organizational outcomes overall ( = 0.36), and on specific form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
427
1
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(465 citation statements)
references
References 127 publications
(151 reference statements)
21
427
1
16
Order By: Relevance
“…Prior research [18,22,34,65] has suggested that managerial coaching and mentoring have a critical impact on developing employees' potential capabilities. As uncertainty makes predicting the future impossible and complexity increases, the sustainability of enterprises has become dependent on finding ways to realize and improve employees' potential capabilities.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research [18,22,34,65] has suggested that managerial coaching and mentoring have a critical impact on developing employees' potential capabilities. As uncertainty makes predicting the future impossible and complexity increases, the sustainability of enterprises has become dependent on finding ways to realize and improve employees' potential capabilities.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Managerial coaching is not the same as teaching the existing solutions directly but is targeted at encouraging the self-discovery of what the coachee wants to achieve and at facilitating learning [12,13,21]. Therefore, mutual respect and trust between the coach and the coachee are critical to the effectiveness of coaching [22]. Managerial coaching has received particular attention as a core activity that must be performed by managers [23,24].…”
Section: Managerial Coachingmentioning
confidence: 99%
“…Despite the evidence obtained from research that suggests that executive coaching may be an effective leadership development strategy, insufficient research has been done that demonstrates the impact of theoretically substantiated and appropriately designed coaching interventions on the ESCs of leaders. It has been broadly articulated that adequate theory building in respect of the effectiveness of specific development processes and outcomes is dependent on a sufficient number of welldesigned and informative research studies (Groves et al 2008;Jones et al 2016;Theeboom et al 2014). This study aimed to develop a template of what can be considered an informative study on the impact of coaching on the emotional and social intelligence competencies of leaders.…”
Section: Resultsmentioning
confidence: 99%
“…Recent meta-analytical studies by Theeboom, Beersma and Van Vianen (2014) and Jones, Woods and Guillaume (2016) show promising findings suggesting that coaching has significantly positive effects on various outcomes on different levels, for example, on organisational, affective, skills-based and individual (achievement, performance) levels. These meta-analysis studies indicate that coaching can be an effective intervention in organisations.…”
Section: The Efficacy Of Executive Coaching In Leadership Developmentmentioning
confidence: 99%
See 1 more Smart Citation